Damage degradation law of mechanical properties of sandstone under different water-rich states - He, Xiaolang; Hu, Xin; Pu, Zhiguo; Chen, Deming; Duan, Dongwei; Han, Gang; Xie, Jiahao; Zhang, Yin (Frontiers in Earth Science, 2024)
Safety is the primary guarantee for achieving coal mine production. The degree of water in the overlying rock of the coal seam has a significant impact on the mechanical strength of the rock, which can lead to subsidence, roof collapse, and rock burst in the mining area. Therefore, it is important to study the law of water-rich damage and deterioration of coal seam overlying rock, as well as the characteristics of bursting liability to prevent and control mining disasters. This paper aims to investigate the change in compressive strength, elastic modulus, and bursting liability of coal measure strata under different water content and their relationship with lithology, particle size, pore characteristics, and mineral characteristics. We carried out uniaxial compression tests on drilled and prepared samples of coal measure strata in the east of Ordos City. We also monitored the acoustic emission characteristics of the rock failure process under different water content. The results demonstrate that, in the dry state, the compressive strength of siltstone >fine sandstone >medium sandstone >coarse sandstone. As the water content increases, the rock transitions from brittle to plastic, and the compressive strength, elastic modulus, and bursting liability gradually decrease. The stress-strain curve changes from a single peak to bimodal and multimodal, and the active degree of acoustic emission events decreases, especially the low-value ringing count. Calcareous cementation, clay minerals, and chlorite exhibit strong softening properties when subjected to water, while the grain skeleton (comprising quartz, feldspar, mica) and siliceous cementation displays weak softening properties in such conditions. The most significant is the mechanical strength deterioration of siltstone containing a clay matrix. The research findings can provide reference and theoretical support for safe mining practices in coal mines.